2019
DOI: 10.3390/molecules24224129
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Biological Evaluation of Novel Aminochalcones as Potential Anticancer and Antimicrobial Agents

Abstract: A series of 18 aminochalcone derivatives were obtained in yields of 21.5–88.6% by applying the classical Claisen-Schmidt reaction. Compounds 4–9, 14 and 16–18 with 4-ethyl, 4-carboxy-, 4-benzyloxy- and 4-benzyloxy-3-methoxy groups were novel, not previously described in the scientific literature. To determine the biological properties of the synthesized compounds, anticancer and antimicrobial activity assays were performed. Antiproliferative potential was evaluated on four different human colon cancer cell lin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
41
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(43 citation statements)
references
References 35 publications
1
41
0
1
Order By: Relevance
“…They were tested against reference strains of E. coli, S. aureus, and B. subtilis from the American Type Culture Collection (ATCC). For example, 7,4′-di- O -isopropylnaringenin ( 5a ) was inactive against Escherichia coli , Bacillus subtilis, and S. aureus , whereas 7,4′-di- O -isopropylnaringenin oxime ( 5b ) exhibited activity against B. subtilis and S. aureus with MIC values equal to 6.25 μg/mL and 12.5 μg/mL, respectively [ 40 ]. The obtained results prompted us to carry out research on pathogens that are currently clinically relevant.…”
Section: Resultsmentioning
confidence: 99%
“…They were tested against reference strains of E. coli, S. aureus, and B. subtilis from the American Type Culture Collection (ATCC). For example, 7,4′-di- O -isopropylnaringenin ( 5a ) was inactive against Escherichia coli , Bacillus subtilis, and S. aureus , whereas 7,4′-di- O -isopropylnaringenin oxime ( 5b ) exhibited activity against B. subtilis and S. aureus with MIC values equal to 6.25 μg/mL and 12.5 μg/mL, respectively [ 40 ]. The obtained results prompted us to carry out research on pathogens that are currently clinically relevant.…”
Section: Resultsmentioning
confidence: 99%
“…The inhibition activity of 1 against Escherichia coli ATCC 25923 and Candida albicans ATCC 10231 was as strong as the antibiotic sulfamerazine and as strong as sulfadiazine against Staphylococcus aureus ATCC 25922. The antibacterial and antifungal activities against different strains were also tested by Kozłowska et al [ 42 ], as shown in Table 2 .…”
Section: -Nh 2 -Substituted Aminochalconesmentioning
confidence: 99%
“…Compound 1 causes complete growth inhibition in the case of S. aureus DSM799 and A. niger DSM1957 microbial strains and showed significant prevention of growth for the other strains [ 42 ]. The results of these investigations [ 40 , 42 ] show 1 as a promising antibacterial agent.…”
Section: -Nh 2 -Substituted Aminochalconesmentioning
confidence: 99%
See 2 more Smart Citations